Video-assisted peer teaching for surgical skills training - innovative potential for the medical curriculum and beyond: a randomized controlled trial - Böcker, Arne Hendrik; Bank, Corinna; Kim, Bong-Sung; Aman, Martin; Pears, Kim Hannah; Klasen, Martin; Lambert, Sophie; Sopka, Saša (Journal of surgical education, 2022)
Objective - Hygienic healthcare standards are essential for avoiding hospital infections. However, medical students and staff lack training in this field, which may be due to high personnel resources of present educational approaches. Thus, there is an urgent need for a novel and efficient approach. Aim of the study is to compare a newly developed video-assisted peer feedback (VAPF) method for teaching wound dressings to the traditional teaching method with qualified instructor feedback (QIF) with respect to essential learning outcomes. - Design, Setting and Participants - In this randomized controlled noninferiority trial, 251 medical undergraduates were randomly assigned to one of two interventions (QIF n=127; VAPF n=124). In QIF, participants received feedback from a qualified instructor. In VAPF, participants video-recorded each other while performing a wound dressing and gave each other feedback assisted by a standardized checklist. Outcome measures were participants’ score in an objective structured practical examination (OSPE) and a written exam after the course. - Results - Noninferiority of VAPF (n=123) compared to QIF (n=127) was confirmed for both OSPE (QIF: 8.83 ± 1.30; VAPF: 8.88 ± 1.04; mean difference -0.04, 95% CI -0.34 to 0.25) and written exam (QIF: 8.99 ± 1.06; VAPF: 9.14 ± 1.05; mean difference -0.15, 95% CI -0.41 to 0.12). - Conclusions - VAPF is a cost-efficient and viable alternative to QIF commonly used in medical education. It provides comparable training outcomes to the traditional training method with lower personnel investment. VAPF is a promising educational method for improving essential clinical competencies.